Identification of Potent siRNA Delivery Peptides Using Computer Modeling - Ke Men; Mohan Liu; Xueyan Zhang; Yuling Yang; Rui Zhang; Yusi Wang; Die Hu; Bailing Zhou; Li Yang (Advanced Science, 2024)
Abstract Peptides with suitable aggregation behavior and electrical properties are potential siRNA delivery vectors. However, identifying suitable peptides with ideal delivery and safety features is difficult owing to the variations in amino acid sequences. Here, a holistic program based on computer modeling and single‐cell RNA sequencing (scRNA‐seq) is used to identify ideal siRNA delivery peptides. Stage one of this program consists of a sequential screening process for candidates with ideal assembly and delivery ability; stage two is a cell subtype‐level analysis program that screens for high in vivo tissue safety. The leading candidate peptide selected from a library containing 12 amino acids showed strong lung‐targeted siRNA delivery capacity after hydrophobic modification. Systemic administration of these compounds caused the least damage to liver and lung tissues and has little impact on macrophage and neutrophil numbers. By loading STAT3 siRNA, strong anticancer effects are achieved in multiple models, including patient‐derived xenografts (PDX). This screening procedure may facilitate the development of peptide‐based RNA interference (RNAi) therapeutics.